The thinnest, steepest, and maximum elevation Corneal locations in noncontact and contact lens wearers in keratoconus - Romero-Jimenez, Miguel (2013)
PURPOSE:: To assess the relationship between the thinnest corneal location and the steepest and maximum elevation corneal locations in subjects with keratoconus and the effect of gas permeable contact lens wear on the location of these points. METHODS:: Sixty-one consecutive subjects (98 eyes) with keratoconus. Thirty-one (49 eyes) and 30 (49 eyes) subjects were gas permeable contact lens (CL-W) and non-contact lens wearers (N-CL), respectively. Thinnest, steepest, and maximum elevation corneal locations were evaluated from topographies collected with Pentacam Eye Scanner. RESULTS:: In the entire sample and in N-CL and CL-W, the thinnest location does not overlap with the steepest or maximum elevation corneal locations (all P > 0.05). The thinnest and maximum tangential curvature locations were found to be located further away from the geometric center of the cornea in CL-W versus N-CL (P < 0.05). CONCLUSION:: The thinnest corneal location does not overlap with maximum axial and tangential curvatures or with the front and back elevation locations in keratoconus subjects. Contact lens wear does not affect this lack of overlapping.